Hak atas Kekayaan Intelektual ImplementasInya dalam BIdang SenI Rupa - BasKoRo S. BanIndRo (Ars: Jurnal Seni Rupa dan Desain, 2010)
Intellectual Property Right and Its Implementation in Visual Art. The works of  visual art, the fine art and the  applied ones, are basically the results of  artistic creative  processes that have to be protected legally. The artists’capability in cultivating their ideas and creations in visual forms is a part of  their Intellectual Properties. It certainly  will provide the holders not only the economic values but also the spirit and motivation to improve their creative competence. Intellectual Property Right as one of  the legal protection devices is expected to be understood and accepted  by all artists, art lovers, designers, and art creators so that visual art  will dynamically develops and functions as a tool in the practice of  social control and correction with  any role they play:  contributors, sponsors or stake holders.